Uji Efektitivitas Sediaan Gel Ekstrak Daun Kemangi (Ocimum basilicum L) Terhadap Penyembuhan Luka Sayatan Tikus Putih (Rattus nornvegicus) - Anastasia Walukow; Douglas N. Pareta; Silvana L. Tumbel; Joke L. Tombuku; Christel N. Sambou (Journal of Pharmaceutical and Sciences, 2023)
Natural wealth has a variety of herbal plants, plants that are included in it efficacious as medicine. Traditional medicine, is an ingredient or herb that is usually used as traditional medicine and is used to accelerate the healing of diseases, one of the plants used to accelerate wound healing is basil leaves (Ocimum basilicum L.). This study aimed to determine the effectiveness of basil leaf gel preparations against wound healing in white rats (Rattus norvegicus). The test animals used were 15 rats. A 1 cm cut wound is made on the back of the mouse using a scalpel. The method used in this study is in the form of laboratory experiments. This study used a Complete Randomized Design (CDR) consisting of 5 treatments, including 1 negative control, 1 positive control (bioplacenton), and 3 stratified concentrations, namely 5% concentration gel, 10% concentration gel and 15% concentration gel with 3 repetitions each. The treatment is carried out for 7 days. The results of measuring wound diameter in rats based on the results showed that basil leaf extract gel concentration of 15% provided a healing effect more effective than other extracts.